Political activity for physical activity: health advocacy for active transport - Amun Qa-; Reeder Anthony I; Murdoch Linda; Richards Rosalina (BMC, 2011)
Abstract Effective health advocacy is a priority for efforts to increase population participation in physical activity. Local councils are an important audience for this advocacy. The aim of the current study was to describe features of advocacy for active transport via submissions to city council annual plans in New Zealand, and the impact of an information sheet to encourage the health sector to be involved in this process. Written submissions to city council's annual consultation process were requested for 16 city councils over the period of three years (2007/08, 2008/09, and 2009/10). Submissions were reviewed and categories of responses were created. An advocacy information sheet encouraging health sector participation and summarising some of the evidence-base related to physical activity, active transport and health was released just prior to the 2009/10 submission time. Over the period of the study, city councils received 47,392 submissions, 17% of which were related to active transport. Most submissions came from city residents, with a small proportion (2%) from the health sector. The largest category of submissions was in support of pedestrian and cycling infrastructure, design and maintenance of facilities and additional features to support use of these transport modes. Health arguments featured prominently in justifications for active transport initiatives, including concerns about injury risk, obesity, physical inactivity, personal safety and facilities for people with disabilities. There was evidence that the information sheet was utilised by some health sector submitters (12.5%), providing tentative support for initiatives of this nature. In conclusion, the study provides novel information about the current nature of health advocacy for active transport and informs future advocacy efforts about areas for emphasis, such as health benefits of active transport, and potential alliances with other sectors such as environmental sustainability, transport and urban planning and local communities.